Bounce cosmology from F(R) gravity and F(R) bigravity; Journal of Cosmology and Astroparticle Physics; Vol. 214 - Bamba K.; Makarenko A. N.; Myagky A. N. Alexander Nikolayevich; Nojiri Sh.; Odintsov S. D. (2014, 2014)
Title screen